Facilitating Black identity and advocacy: creating cellphilms for reflecting on issues affecting Black students. Issue 1 (15th March 2022) - Noreiga, Alicia
Abstract : Ethical facilitation is of paramount importance if educators are to address the issues that plague Black students. This paper presents an autoethnographic account of my experiences facilitating two cellphilm workshops with self-identified Black university students attending two universities in New Brunswick, Canada. Nestled within African-Canadian Feminist discourse, I explore my positionality as a Black international female student. I reflect on the ways my racial awareness and experiences led me to employ participatory arts-based methodologies to empower Black university students to vocalize their experiences and disrupt the hemogenic White dominance and anti-Black racism in academia. I describe being approached by a pair of White faculty members to facilitate two cellphilm workshops, engaging in pre-workshop planning and first cellphilm workshop, and the ways I engaged in ethical praxis to stimulate trust and create a supportive environment for participants. I next describe creating a cellphilm as a support mechanism in response to participants' cellphilms. Finally, I examine post-production activities that took my facilitation and activism beyond cellphilm creation as I reflect on how I disseminated and capitalized on my various positions within the university to raise awareness of racist practices that exclude and marginalize Black students.